The influence of sub-technique and skiing velocity on air drag in skating style cross-country skiing - Elfmark, O.; Docter, H.; Sandbakk, Ø.; Kocbach, J. (Sports Engineering, 2023)
In cross-country skiing, velocities range from 2 m s-1 up to more than 20 m s-1 across undulating terrain, and aerodynamics can, therefore, make a large impact on performance. The aim of this study was to investigate the influence of skiing velocity on air drag for skating sub-techniques and downhill postures (tuck). Dynamic and static drag measurements for two athletes were performed in a wind tunnel in relevant velocity ranges for each sub-technique. The drag area decreased with velocity from 2 m s-1 to around 10-12 m s-1, where it plateaued. No difference in air drag was found between the sub-techniques performed in upright postures (G2-G4) and thereby relatively similar frontal areas. In the G5 sub-technique performed without poling action in a lower posture, the reduced air drag was approximately 28% lower than for G2-G4 at similar velocities, and could even be reduced by an additional 21.7% by keeping the arms tucked in front of the body. In the downhill tucked postures, athletes could reduce air drag by 23% by keeping a low tuck, compared to a high tuck with straight legs. The sub-techniques were tested both dynamically and by averaging the static positions throughout the movements. The air drag was on average 6.1% lower for dynamic movements, indicating that dynamical movements like in cross-country skiing should be tested dynamically when evaluating air drag. Finally, the chosen cycle rate had minimal influence on air drag.